2022
DOI: 10.1039/d2nj03719j
|View full text |Cite
|
Sign up to set email alerts
|

Serendipitous synthesis of 2-alkenyl- and 2-aryl-4-thiazolidinones using dithiodiglycolic anhydride

Abstract: Dithiodiglycolic anhydride undergoes an efficient formal cycloaddition with imines to afford functionalized 4-thiazolidinones, without complications arising from the anhydride-imine reaction or the sulfa-Michael reaction (in the case of 1,3-azadienes).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Interestingly, Beng and co-workers have recently shown that the thiodiglycolic anhydride ( 189 ) does not undergo CCR with imines ( 15 ). Conversely, a formal [3+2] cycloaddition efficiently leads to functionalized 4-thiazolidinones ( 190 , Scheme 56 ) [ 99 ].…”
Section: Two-component Castagnoli–cushman Reactions (2c-ccr)mentioning
confidence: 99%
“…Interestingly, Beng and co-workers have recently shown that the thiodiglycolic anhydride ( 189 ) does not undergo CCR with imines ( 15 ). Conversely, a formal [3+2] cycloaddition efficiently leads to functionalized 4-thiazolidinones ( 190 , Scheme 56 ) [ 99 ].…”
Section: Two-component Castagnoli–cushman Reactions (2c-ccr)mentioning
confidence: 99%
“…The conventional method for the synthesis of 4‐thiazolidinones involved the reaction of amine, carbonyl compound, and mercaptoacetic acid using different catalysts via a two‐step strategy [16] ( route a , Figure 5). The reaction of acid hydrazide with aldehydes afforded corresponding hydrazones, which on further reaction with thioglycolic acid provided 2‐substituted 4‐thiazolidinone analogs [17] ( route b , Figure 5). Esters on reaction with thiosemicarbazide afforded hydrazine carbothioamides, which undergo heterocyclization with chloroacetic acid in the presence of sodium acetate to get thiazolidin‐4‐one derivatives [18] ( route c , Figure 5).…”
Section: Introductionmentioning
confidence: 99%